402. Clinical Characteristics and Outcome of Staphylococcus lugdunensis Prosthetic Joint Infections - Masood, Komal (Open Forum Infect Dis, 2019)
BACKGROUND: Although Staphylococcus lugdunensis is a coagulase-negative staphylococcus, it shares similar characteristics with S. aureus and is increasingly recognized as the cause of serious infections, including prosthetic joint infections (PJIs). The aim of this study was to determine the clinical characteristics and outcome of S. lugdunensis PJIs. METHODS: This was a retrospective multicenter study conducted from January 2007 through December 2017 involving consecutive adult patients with S. lugdunensis PJIs in northwest Ohio. Clinical and microbiologic characteristics, treatment modalities and outcome were evaluated. RESULTS: A total of 695 patients were evaluated and 29 (4%) patients met inclusion criteria (Table 1). All patients were Caucasian and 52% were female with a median age 68.8. Comorbidities included Diabetes Mellitus (34%), CAD (41%), CHF (20%), COPD (20%) and cancer (14%). The most common clinical presentations were pain (28/29, 97%), decreased range of motion (27/29, 93%) and joint swelling (21/29, 72%). Two patients had concomitant bacteremia. Knee was the most commonly affected joint (69%), followed by hip (24%). All isolates, except one, were susceptible to oxacillin. Thirteen (45%) patients had a two-stage revision, nine (31%) debridement with/without revision, six (21%) no surgical intervention and one (3%) a 1-stage revision. The majority of patients (71%) received ≥4 weeks of antibiotics (abx). Two patients with no surgical intervention and one with debridement received no abx. Another was discharged to hospice without intervention. Relapse was observed in two (15%) patients who had a 2-stage revision, four (44%) who had debridement, 6 (100%) who had no surgical intervention or 1-stage revision. Overall, there was a statistically significant difference in cure rates in patients who underwent 2-stage revision compared with other treatment modalities (P = 0.003) regardless of abx treatment regimen, including prolonged IV abx therapy. However, IV abx were superior to oral (P = 0.009). CONCLUSION: Appropriate management of S. lugdunensis PJIs includes both aggressive surgical management with a prolonged course of abx with excellent clinical responses. Relapse is high in patients treated without two-stage revision irrespective of route or duration of abx therapy. DISCLOSURES: All authors: No reported disclosures.